Doctor Maisy - Cousins, Lucy.; King Rollo Films, Ltd. (Cambridge, Mass. : Candlewick, 2001)
Maisy the mouse and Tallulah the bird play hospital, practicing their doctoring and nursing skills on Panda and dealing with another subsequent health crisis.
"First published by Walker Books ... London"--P. facing t.p.
"Based on the audio visual series 'Maisy.' A King Rollo Films Production for Universal Pictures Visual Programming. Original script by Andrew Brenner"--P. facing t.p.
1.3
K-3
K-3
School Library Journal
Keywords: Mice -- Fiction; Physicians -- Fiction; Play -- Fiction; Maisy (Fictitious character : Cousins) -- Fiction; Mice -- Fiction; Physicians -- Fiction; Play -- Fiction; Maisy (Fictional character : Cousins) -- Fiction